The star forming region Monoceros R2 as a gamma-ray source - Martí, J. (2013)
Context. After the release of the gamma-ray source catalog produced by the Fermi satellite during its first two years of operation, a significant fraction of sources still remain unassociated at lower energies. In addition to well-known high-energy emitters (pulsars, blazars, supernova remnants, etc.), theoretical expectations predict new classes of gamma-ray sources. In particular, gamma-ray emission could be associated with some of the early phases of stellar evolution, but this interesting possibility is still poorly understood. Aims. The aim of this paper is to assess the possibility of the Fermi gamma-ray source 2FGL J0607.5-0618c being associated with the massive star forming region Monoceros R2. Methods. A multi-wavelength analysis of the Monoceros R2 region is carried out using archival data at radio, infrared, X-ray, and gamma-ray wavelengths. The resulting observational properties are used to estimate the physical parameters needed to test the different physical scenarios. Results. We confirm the 2FGL J0607.5-0618c detection with improved confidence over the Fermi two-year catalog. We find that a combined effect of the multiple young stellar objects in Monoceros R2 is a viable picture for the nature of the source.